Analisa Dan Perbandingan Algoritma Whirpool Dan Sha-512 Dalam Penyandian Data Gambar - Darwis Pardamean Purba (Bulletin of Artificial Intelligence, 2022)
Image file is a form of collaboration which is located between points, lines, fields and also colors which will be very useful for imaging something, digital images are representations of light intensity functions in discrete form on a two-dimensional plane. An image file can be said to be original or original if the image does not experience the slightest change in any structure of an image. Manipulation of a file often occurs and is carried out by irresponsible people to provide benefits for that person, it is necessary to have a technique used to maintain the originality of a file or detect the authenticity of the image file, a technique can be used, namely Cryptography techniques. Cryptography is a science that studies how to keep data or messages safe when sent, from sender to recipient without experiencing any interference from irresponsible parties. A hash function is a one-way function that converts a set of strings into a set of strings whose size is smaller than the original size. The hash function has many uses, such as to maintain data integrity, delivery time efficiency, and to minimize the length of diverse data. The real-world applications of hash functions vary, such as being used to check the originality of data, to store keywords in databases, and much more. In this study, 2 existing hash functions will be discussed, namely the SHA-512 hash function, and the whirlpool hash function. SHA-512 is a variant of SHA-2 designed by the National Security Agency (NSA), while the Whirlpool hash algorithm was developed by 2 people, Vincent Rijmen and Paulo S.L.M. Barreto. These two hash functions are hash functions that are considered to have high security. In these two hash algorithms, there is still no collision in the hash value. This study will discuss the differences and similarities of the two algorithms